2022
DOI: 10.1038/s41467-022-32813-z
|View full text |Cite
|
Sign up to set email alerts
|

Early macrophage response to obesity encompasses Interferon Regulatory Factor 5 regulated mitochondrial architecture remodelling

Abstract: Adipose tissue macrophages (ATM) adapt to changes in their energetic microenvironment. Caloric excess, in a range from transient to diet-induced obesity, could result in the transition of ATMs from highly oxidative and protective to highly inflammatory and metabolically deleterious. Here, we demonstrate that Interferon Regulatory Factor 5 (IRF5) is a key regulator of macrophage oxidative capacity in response to caloric excess. ATMs from mice with genetic-deficiency of Irf5 are characterised by increased oxidat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…A recent study by Orliaguet et al . has shown that IRF-5 regulates the mitochondrial architecture remodelling by transcriptionally repressing a key mitochondrial component for oxidative respiration, namely GHITM (55). This work was done in macrophages and in the context of a high-fat diet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Orliaguet et al . has shown that IRF-5 regulates the mitochondrial architecture remodelling by transcriptionally repressing a key mitochondrial component for oxidative respiration, namely GHITM (55). This work was done in macrophages and in the context of a high-fat diet.…”
Section: Resultsmentioning
confidence: 99%
“…The second study by Orliaguet et al demonstrates that IRF-5-deficient macrophages have a highly oxidative nature in the context of a short-term high fat diet. This was caused by transcriptional de-repression of the mitochondrial matrix component Ghitm , which is a direct target of IRF-5 (55). GHITM is an inner membrane protein that maintains mitochondrial architecture for efficient oxidative phosphorylation (61) and de-repression of Ghitm in Irf5 -/- macrophages results in an increased oxygen consumption rate (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end point of each condition, an OCR assay was performed using compounds in assay media (supplemented with 5.6 mM glucose) at the following concentrations: Oligomycin (1 µM), FCCP (2 µM), and Rot/AA (0.5 µM) (Cat# 103015-100; Agilent Technologies Seahorse XF Cell Mito Stress Test Kit, Santa Clara, CA, USA). The levels of basal and maximal respirations were calculated, and OCR was normalized to the extracted total protein as an indirect estimation of the number of cells [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the end point of each condition, an OCR assay was performed using compounds in assay media (supplemented with 5.6 mM glucose) at the following concentrations: Oligomycin (1 μM), FCCP (2 μM), and Rot/AA (0.5 μM) (Cat# 103015-100; Agilent Technologies Seahorse XF Cell Mito Stress Test Kit, Santa Clara, CA, USA). The levels of basal and maximal respirations were calculated, and OCR was normalized by the number of cells [30].…”
Section: Metabolic Flux Analysis (Seahorse Assay)mentioning
confidence: 99%